Mites (Mesostigmata, Prostigmata, Astigmatina) associated with weeds among physic nut crops (Jatropha curcas l.: Euphorbiaceae) in Brazil - Rezende, José Marcos [UNESP] (2012)
A better knowledge of the mite fauna that lives on weeds among crop plants is relevant to the determination of appropriate crop management, as these plants may support reservoirs and/or be alternative hosts for predatory or phytophagous mites important to the cultivated plants. In this study, a survey of the mite fauna from 20 weed species found in four plantations of Physic nut (Jatropha curcas L.) (Euphorbiaceae) in Brazil was carried out between May 2008 and May 2009. Mites belonging to the Mesostigmata, Prostigmata and Astigmatina (= Astigmata) were identified and, altogether, 38 species were found. Three species of plants stood out as hosts of the greatest variety of mites: Glycine wightii Wight & Arn. (18 species), Sida santaremnensis Monteiro (16) and Tridax procumbens L. (17). Glycine wightii and S. santaremnensis supported similar ranges of predators and phytophages, while T. procumbens stood out by hosting the largest number of predatory species compared to phytophages. The most commonly found mite was Pronematus sp. (Iolinidae), occurring on 18 of the 20 plants analyzed. © 2012 Systematic & Applied Acarology Society.